Investigating dietary behaviours in a category 1 professional football academy - Levington, A.; Myrissa, K.; Pilic, L.; Fleming, J.; Hulton, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Academy footballers` energy intake, energy expenditure, and nutrition knowledge are of key interest amongst researchers and applied practitioners. The study aimed to investigate academy footballers` knowledge, dietary intake, and energy expenditure in an applied setting. Academy male footballers were recruited from a Category 1 professional football academy playing in the youth development phase (under 12s - under 16s). Twenty-five academy footballers completed a self-reported 7-day food diary. Eighty-three academy footballers completed The Nutrition Sport Knowledge Questionnaire (NSKQ) an 87-item validated questionnaire) to assess nutrition knowledge. Energy expenditure was estimated by a global positioning system (Athlete Tracking System, Catapult, Victoria, Australia) during a 7-day football training week. The U12 to U15s completed three training sessions (78 ± 20minutes per session) compared to the U16s which completed two training session (90 ± 0 minutes per session) Mean training energy expenditure was that the U12s (n = 8, 573 ± 205 kcal) and U15s (n = 11, 543 ± 151 kcal) energy expenditure during football training was significantly greater when compared to under 13s (n = 13, 409 ± 57 kcal), under 14s (n = 13, 371 ± 178 kcal), and 16s (n = 12, 404 ± 79 kcal) during their respective training week. There were no significant differences in energy intake between age groups; U12s (n = 7): 1719 ± 194 kcal/d, U13s (n = 9): 1770 ± 312 kcal/d, U14s (n = 4): 1836 ± 425 kcal/d, and U16s (n = 4):1624 ± 805 kcal/d; (p<0.05). Nutrition knowledge scores were indicative of poor knowledge (mean 33% ± 7, range 8%-48%), and no significant differences in knowledge between age groups. Nutrition knowledge and energy intake did show a negative correlation (r= -.144, p= -0.491). These findings show that players had low knowledge and dietary intake which highlights the importance of qualified sports nutritionists to investigate new strategies to improve nutrition in academy footballers.